MECHANISM ANTAGONISM of Trichoderma viride AGAINST SEVERAL TYPES of PATHOGENS and PRODUCTION of SECONDARY METABOLITES - Anton Muhibuddin; Endah Mulyaningtyas Setiyowati; Antok Wahyu Sektiono (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Biological control agents using antagonistic fungi have the ability to inhibit the development of disease-causing pathogens by various mechanisms such as competition for space and nutrients, antibiosis by producing antibiotics in the form of chemical compounds, and parasitism by entangling pathogenic hyphae. Antibiotic mechanism is a condition in which an organism secretes one or more metabolites that have a negative effect on other organisms. One of the fungi that has the ability as an antibiosis is Trichoderma viride, where this fungus secretes secondary metabolites in the form of a viridiol phytotoxin compound. This study conducted to determine the antagonist mechanism of the fungus T. viride in suppressing the growth of Alternaria solani, Fusarium oxysporum, Rhizoctonia solani, and Sclerotium rolfsii which causes disease in some cultivated plants, as well as what compounds T. viride possesses in suppressing the growth of other pathogens. This research was carried out at the Plant Disease Laboratory, Department of Plant Pest and Disease, Faculty of Agriculture, Brawijaya University from November 2020 to August 2021. The research was conducted using Trichoderma viride as antagonist fungus and Alternaria solani, Fusarium oxysporum, Rhizoctonia solani, and Sclerotium rolfsii as pathogenic fungi. This research consisted of 3 stages, the first stage was rejuvenation and macroscopic and microscopic characterization of pathogenic fungi and antagonist fungi. The second stage is the in vitro antagonist test using the dual culture method using a completely randomized design with 6 replications. The third stage is the phytochemical test of secondary metabolites using 5 test, namely terpenoid and steroid test, the alkaloid test, the flavonoids test, the tannin test, and the saponin test. The results showed that T. viride had an inhibitory ability >50% against four types of pathogens. The mechanism of T. viride antagonist against four treatments, three treatments belonged to the competition mechanism and one treatment belonged to the microparasite mechanism. The content of secondary metabolites of T. viride are steroids and alkaloids.